2008
DOI: 10.1111/j.1365-2125.2008.03238.x
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz concentrations in HIV‐infected patients with and without viral hepatitis

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • HIV‐1 co‐infection with HBV/HCV is the most important factor determining efavirenz‐induced liver toxicity. Higher efavirenz plasma concentrations have been reported in these patients facilitating concentration drug‐related adverse effects. • It is not known whether changes in efavirenz disposition are due to the hepatitis infection/inflammation or to liver failure. As a consequence, the guidelines for the application of therapeutic drug monitoring of efavirenz in HBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
3
8
2
Order By: Relevance
“…Prior studies have demonstrated high efavirenz concentrations among coinfected patients with cirrhosis, as a result of the impact of impaired liver function on efavirenz metabolism . No differences in efavirenz concentration have been reported in HBV‐ or HCV‐coinfected patients without cirrhosis when compared with HIV‐monoinfected patients ; however, one report showed a high efavirenz concentration in HCV‐monoinfected patients without liver cirrhosis . Patients with HBV or HCV infection in our study did not have cirrhosis.…”
Section: Discussionsupporting
confidence: 88%
“…Prior studies have demonstrated high efavirenz concentrations among coinfected patients with cirrhosis, as a result of the impact of impaired liver function on efavirenz metabolism . No differences in efavirenz concentration have been reported in HBV‐ or HCV‐coinfected patients without cirrhosis when compared with HIV‐monoinfected patients ; however, one report showed a high efavirenz concentration in HCV‐monoinfected patients without liver cirrhosis . Patients with HBV or HCV infection in our study did not have cirrhosis.…”
Section: Discussionsupporting
confidence: 88%
“…The failure to find a significant influence of gender on efavirenz exposure, although such an influence has previously been reported [4,7], may have been a result of the skewed gender balance, as there were twice as many female as male participants. The effect of total bilirubin on efavirenz exposure previously reported [16] was not observed in this study; however, such a failure to observe any effect of parameters related to liver function has been documented before, and has been found in HIVinfected patients coinfected with hepatitis [25,26].…”
Section: Discussioncontrasting
confidence: 46%
“…Other NNRTIs have shown similar increases in hepatitis C coinfected patients, although conflicting data exist with respect to both efavirenz and nevirapine. 20 , 21 , 22 , 23 , 24 The change in the apparent oral clearance of etravirine was negligible (+8.3%) in subjects with hepatitis B coinfection, and a 24% decrease was observed in subjects with hepatitis C coinfection. The importance of this finding is limited by the relatively small number of patients with hepatitis B and/or C coinfection and by the exclusion of coinfected patients with markedly elevated liver enzymes.…”
Section: Discussionmentioning
confidence: 96%